Development of SSR Markers Based on Transcriptome Sequencing and Association Analysis with Drought Tolerance in Perennial Grass Miscanthus from China - Nie, Gang; Tang, Lu; Zhang, Yajie; Huang, Linkai; Ma, Xiao; Cao, Xin; Pan, Ling; Zhang, Xu; Zhang, Xinquan (Frontiers in Plant Science, 2017)
Abstract: Drought has become a critical environmental stress affecting on plant in temperate area. As one of the promising bio-energy crops to sustainable biomass production, the genus Miscanthus has been widely studied around the world. However, the most widely used hybrid cultivar among this genus, Miscanthus× giganteus is proved poor drought tolerance compared to some parental species. In this study, we mainly focused on one of the progenitors of M. × giganteus, Miscanthus sinensis, which provide a comparable yield and well abiotic stress tolerance in some places. The main objectives were to characterize the physiological and photosynthetic respond to drought stress and to develop simple sequence repeats (SSRs) markers associated with drought tolerance by transcriptome sequencing within an originally collection of 44 Miscanthus genotypes from southwest China. Significant phenotypic differences were observed among genotypes, and the average of leaf relative water content (RWC) were severely affected by drought stress decreasing from 88.27% to 43.21%, which could well contribute to separating the drought resistant and drought sensitive genotype of Miscanthus. Furthermore, a total of 16,566 gene-associated SSRs markers were identified based on Illumina RNA sequencing under drought conditions, and 93 of them were randomly selected to validate. In total, 70 (75.3%) SSRs were successfully amplified and the generated loci from 30 polymorphic SSRs were used to estimate the genetic differentiation and population structure. Finally, two optimum subgroups of the population were determined by structure analysis and based on association analysis, 7 significant associations were identified including 2 markers with leaf RWC and 5 markers with photosynthetic traits. With the rich sequencing resources annotation, such associations would serve an efficient tool for Miscanthus drought response mechanism study and facilitate a genetic improvement of drought resistant for this species.